Examination of French bean on organic and conventional farming of Research Centre of Nyíregyháza - Györgyi, Gyuláné (Acta Agraria Debreceniensis, 2009)
This study presents the yield results of some French bean varieties in organic and conventional farming. This study presents the advantage of organic farming in environmental point of view and in nutrition. Sale of organic products is insured, there is solvent demand rather in abroad than in Hungary.In Research Centre of Nyíregyháza had made organic farming since 1994, at present on 74 hectares.In the first trial, variety comparison with 9 yellow podded French beans in organic and conventional farming was conducted. Varieties: Carson, Cherokee, Debreceni sárga, Goldmine, Héliosz, Minidor, Sonesta, Sundance és Unidor. The following parameters were observed: the time of emergence and flowering, number of plants per plot, plant height and flowing green harvest. We weighed yield of the standardized, un-standardized and diseased pod fractions. The results were evaluated statistically with SPSS and Excell softwares.Emergence had all at once, but the plants of organic farming were 5 days earlier at flowering and maturity, than conventional farming.The plants in organic place were more developed than in conventional ones. Emergence was more uniform, the growth and the number of plant were square. Significant difference was not detected in plant height between two places. Most of the varieties examined had better total yield in organic place, than in conventional ones. Deviation depended on variety. ‘Sonesta’ and ‘Debreceni sárga’ had the best yield in both places. Inconventional farming choice can be expanded with ‘Unidor’ and ‘Sundance’. In organic farming choice can be expanded with ‘Minidor’ and ‘Carson’.In both places the Sonesta, Debreceni sárga and Unidor varieties had the most standardized yield per hectare. In organic place Carson variety had good pod yield because it was infected less by diseases.In the another trial we studied inside content values of some varieties on organic and conventional places. The parameters were observed: dry matter-, starch-, crude fibre-, crude protein content and amino acid content.The rates of asparagin or glutamine acid were the highest, which was followed by serin or histidine. In asparagin content was the most deviation between conventional and organic farming.Significant differences were between varieties in dry matter-, starch-, crude fibre-, and crude protein content both on organic and conventional places. Each variety had significant differences between organic and conventional farming.Starch had strong and negative correlation with dry matter, crude fibre and crude protein content.Budai piaci and Minidor varieties and BU-16 variety candidate had higher starch content and lower dry matter, crude fibre and crude protein content on organic place. Sonesta variety had almost equal dry matter content on both places, but crude protein content was higher with 10% and starch content was lower with 6% on organic place, than on conventional place. Paridor variety had almost equal starch content, but it had higher dry matter and crude protein content on organic place.